The Impact of Targeted Social Assistance on Labor Market in Georgia : A Regression Discontinuity Approach - World Bank (Washington, DC, 2015)
This report contributes not only to the existing literature, but also provides suggestions for future policy-design related to the TSA program in Georgia. This study shows that Georgia’s TSA program does generate disincentives to search for jobs or work around the threshold of eligibility, with this effect being concentrated among women. This report is structured as follows: Section two discusses the existing literature and provides a more detailed overview of the TSA program. Section three describes the sampling frame, the sampling method and the data used. Section four explains the empirical approach of the study. Section five elaborates on the main results. Section six concludes with a discussion on policy implications.